Psikoedukasi Penggunaan Internet dan Short Course Keterlibatan Siswa dalam Kegiatan Pembelajaran yang Efektif - Izzanil Hidayati; Putri Sukma Deri; Sherly Safitri (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2023)
Technology and the internet can help students learn effectively. Improper use of online resources accessed for educational purposes can also hinder effective learning, as students need more participation and control. This training encourages students to participate in teaching and learning, even using internet-supported education facilities. The first part of the training was psychoeducation regarding the effectiveness of internet use among teenagers, and the second part was related to a short course regarding student engagement in learning activities. Psychoeducation uses the lecture method, and question-and-answer discussions with participants, and a short-course used the lecture method discussions in small groups of four to five students. The activity's outcomes included increases in participants' pre- and post-test knowledge of internet effectiveness (up from 51% of participants) and student involvement (up from 96.2% of participants). According to the paired sample t-test results, there was a noteworthy distinction between the short-course activities yielded pre-test and post-test scores with a p<.001. On the other hand, the outcomes of the psychoeducational activities pre- and post-test did not differ significantly, a p-value of 0.828. After completing this activity, students are expected to be focused on their academic work and possess the skills necessary to use the internet efficiently.